PENGARUH JUMLAH BLADE SUDU DATAR TERHADAP UNJUK KERJA KINCIR ANGIN - Wibowo, Hary; Rusianto, Toto; Afrilsyah, Rony (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2006)
Wind is one of some alternate energy resources in the nature that used to membantu and easily human activity. The aim of this research known the performance of wind mill. The variable in the research with various number of blade 2,3, and 4. Wind mill for the research had spesification flate blade with 200 from wind direction.The speed of wind and revolution of shaft was measured for calculated power output and teoritical, coefficient performance, efficiency, and torque. Wind turbin tested in Depok resort, Parangtritis - Bantul Yogyakarta.The result of research showed the number two blade had higher revolution (121,7 rpm) than three blade (102,35 rpm) and four blade (116 rpm).The wind velocity increased to cause increase revolution of shaft. Maximum Power and Torque reached on wind turbin with three blade.